Tax Haven Welfare and the Crackdown on Secrecy: Evidence from Night Light Emissions - Hoang Ha Nguyen Thi; Alfons Weichenrieder (Center for Economic Studies and ifo Institute (CESifo), 2023)
Following numerous high-profile international initiatives, tax haven jurisdictions have been nudged into agreeing on tax information exchange. We analyse whether these agreements had measurable effects on the economy of cooperative tax havens. As GDP data are missing for many small tax haven jurisdictions, we use night light data as a proxy for economic activity. Depending on the exact list of tax havens, using this proxy allows us to increase the number of tax haven jurisdictions by up to 25 percent compared to using GDP. We find that tax havens which have signed more tax information exchange agreements experienced a significantly higher economic activity, as proxied by the sum of night light emissions. This applies to agreements that provide information exchange on request as well as agreements that implement automatic information exchange. When we use GDP as a measure of economic activity, tax information exchange agreements are not associated with a differential development of economic activity. Both observations suggest that information exchange treaties so far have not reduced economic growth in more cooperative tax havens.
Keywords: H26; H87; O11; 330; tax haven; night light emissions; tax information exchange; economic development